Activation of ilmenite as an oxygen carrier for solid-fueled chemical looping combustion. (1st July 2017) - Chen, Liangyong; Bao, Jinhua; Kong, Liang; Combs, Megan; Nikolic, Heather S.; Fan, Zhen; Liu, Kunlei
Highlights: Improving ilmenite OC's performance by adding a small amount of foreign elements. Gasification and combustion efficiency are correlated to OC reactivity and selectivity. Strong catalyzed WGSR from K-added OCs play vital role in improving gasification. Cu-coating hinders Fe-element segregation on the ilmenite surface during redox cycle. Ca-, Ni- and Mn-added ilmenite OCs did not show promising prospects. Abstract: Ilmenite ore is one of the promising oxygen carriers (OCs) used for coal-fueled Chemical-Looping Combustion (CLC) for electricity generation and CO2 capture. However, the low reactivity and natural activation of ilmenite OC are two major constrains impeding its application. This effort is to improve ilmenite OC's performance by introducing a small amount of foreign elements, including alkali or alkaline earth metals (K and Ca) and transition metals (Cu, Mn, and Ni). Coating and re-granulation methods were used to prepare OCs where ilmenite ore was the primary constituent. The reactivity, transport capacity, and selectivity of these ilmenite-based OCs with wet syngas, as well as their performances in coal char-fueled CLC were investigated using a TGA, fixed- and fluidized-bed reactors. The addition of K-element significantly improved the OC's reactivity with wet syngas and coal char. The strong catalytic function for WGSR from K-added OCs was found to play a vital role. Cu-coating hindered effectively Fe-element segregation on the surface of ilmenite OC during cyclic reaction, and the OC structural integrity was well maintained. Ca-, Ni- and Mn-added ilmenite OCs did not show promising prospects. The gasification rate and combustion efficiency could be respectively correlated to the reactivity and selectivity of different OCs except for the K-added samples.